A key to pupal exuviae of Neotropical Tanytarsini miptera: Chironomidae) - Wiedenbrug, S.; Torres, R. Ospina (Amazoniana, 2005)
This study presents a key to pupal exuviae of the tribe Tanytarsini from the Neotropical region. Included are the 32 species from the Neotropics presentiy known as pupae, as well as 80 previously unpublished morphotypes from the Brazilian states Rio Grande do Sul and Amazonas. Detailed figures and distributional data are given for all morphotypes.
Keywords: Tanytarsini